PERAN SISTEM INFORMASI AKUNTANSI PADA UMKM DI WILAYAH SUMSEL (STUDI KASUS TRAVEL PO BHW) - Safitri, Rika Henda; Aulia, Bunga; Tharika, Riska (Universitas Ahmad Dahlan, 2019)
This paper aims to analyze and improve the profitability of UMKM in the South Sumatra region. This paper takes samples from travel service UMKM in South Sumatra, namely PO Batang Hari Wisata. PO BHW Travel is one of the travel offices in Palembang, South Sumatra. This company has been serving trips with various routes. This research intends to provide a useful information system for businesses like PO BHW Travel.The type of data used in this study are primary and secondary data. Data collection techniques used in the form of secondary data obtained from trusted journals and articles, as well as from books and other references. Primary data obtained are from the results of field studies through observations about PO BHW Travel. Data obtained from several sources, by conducting interviews with PO BHW Travel owners and direct observation to the business location in the form of ticket sales counters.It is expected that with the existence of an accounting information system, this travel business can overcome problems in its operations, particularly in terms of recording and providing financial information.